Brain pharmacokinetics of anti-transferrin receptor antibody affinity variants in rats determined using microdialysis - Hsueh-Yuan Chang; Shengjia Wu; Yingyi Li; Wanying Zhang; Matthew Burrell; Carl I. Webster; Dhaval K. Shah (mAbs, 2021)
Receptor-mediated transcytosis (RMT) is used to enhance the delivery of monoclonal antibodies (mAb) into the central nervous system (CNS). While the binding to endogenous receptors on the brain capillary endothelial cells (BCECs) may facilitate the uptake of mAbs in the brain, a strong affinity for the receptor may hinder the efficiency of transcytosis. To quantitatively investigate the effect of binding affinity on the pharmacokinetics (PK) of anti-transferrin receptor (TfR) mAbs in different regions of the rat brain, we conducted a microdialysis study to directly measure the concentration of free mAbs at different sites of interest. Our results confirmed that bivalent anti-TfR mAb with an optimal dissociation constant (KD) value (76 nM) among four affinity variants can have up to 10-fold higher transcytosed free mAb exposure in the brain interstitial fluid (bISF) compared to lower and higher affinity mAbs (5 and 174 nM). This bell-shaped relationship between KD values and the increased brain exposure of mAbs was also visible when using whole-brain PK data. However, we found that mAb concentrations in postvascular brain supernatant (obtained after capillary depletion) were almost always higher than the concentrations measured in bISF using microdialysis. We also observed that the increase in mAb area under the concentration curve in CSF compartments was less significant, which highlights the challenge in using CSF measurement as a surrogate for estimating the efficiency of RMT delivery. Our results also suggest that the determination of mAb concentrations in the brain using microdialysis may be necessary to accurately measure the PK of CNS-targeted antibodies at the site-of-actions in the brain.